Recent Advances in Simple Preparation of 3D Graphene Aerogels Based on 2D Graphene Materials - Ding, Meichun; Li, Chenwei (Frontiers in Chemistry, 2022)
Recently, 3D graphene aerogels (3GAs) with high electrical conductivity, excellent mechanical properties and fast mass and electron transport have attracted increasing attentions and shown wide applications (such as flexible electronics devices, sensors, absorbents, catalysis, energy storage devices, solar steam generation devices, and so on). The drying process becomes an important factor limiting the large-scale preparation of 3GAs. Therefore, how to simplify the preparation process plays an important role in the large-scale application of 3GAs. In this paper, we summarize the recent progresses of 3GAs by different drying methods and focus on the effect of robust graphene network on the simple preparation of 3GAs. Besides, the design and synthesis strategies of 3GAs with robust graphene network structures have been systematically discussed. Finally, the emerging challenges and prospective for developing simple preparation and functionalization of 3GAs were outlined. It is expected that our paper will lay a foundation for large-scale preparation and application of 3GAs, and inspire more new ideas in this field.